Brief encounters of cytochrome c. (13th January 2017) - Lyons, Joseph A; Nissen, Poul
Abstract : Transient protein interactions are paramount to life where fast and efficient transfer of information and cargo are often integral to pathways and networks. However, complexes formed by transient protein interactions are often times resistant to direct structural characterization due to their inherent, dynamic nature, so our knowledge to date typically derives from biochemical, biophysical and computational methods. In this issue, Shimada and co‐authors present the crystal structure of the mammalian cytochrome c oxidase in complex with its electron donor cytochrome c, identifying a new class of protein–protein interaction termed "soft and specific". Abstract : The first co‐crystal structure of cytochrome c oxidase and cytochrome c illustrates how transient protein–protein interactions mediate a key step in the electron transport chain.